2014
DOI: 10.3329/bjp.v9i3.18875
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> variation in antibacterial activity plant extracts on <i>Glaucium elegans</i> and saffron (<i>Crocus sativus</i>)

Abstract: The increase in antibiotic resistance has resulted in decreasing number active antimicrobial agents available to treat infections by multi-drug resistant (MDR) bacteria. The aim of this study was to determine the antimicrobial activity of the extracts of Glaucium elegans and Saffron (Crocus sativus) onios plant species against Escherichia coli, Staphylococcus aureus, Salmonella enteritidis, Bacillus anthracis and Proteus by disc diffusion method. The methanol extract of G. elegans was found to have a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Let uss recall that Crocus sativus L. possesses various phytochemical properties that have been linked to its antibacterial activity; this activity has been attributed to the presence of compounds such as safranal and crocin [ 55 57 ], as well as flavonoids such as kaempferol, quercetin, and an isorhamnetin derivative [ 58 ]. These compounds are volatile or water-soluble, enabling them to easily reach contaminating microorganisms and contribute to their destruction [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Let uss recall that Crocus sativus L. possesses various phytochemical properties that have been linked to its antibacterial activity; this activity has been attributed to the presence of compounds such as safranal and crocin [ 55 57 ], as well as flavonoids such as kaempferol, quercetin, and an isorhamnetin derivative [ 58 ]. These compounds are volatile or water-soluble, enabling them to easily reach contaminating microorganisms and contribute to their destruction [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…No inhibitory effect was detected with this method [33]. In another study, 9, 10, 12, 17, and 18 mm inhibition was determined against S. enteritidis, E. coli, S. aureus, B. anthracis, and Proteus, respectively, at G. elegans 750 μg/disc concentration [34].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…This may be ascribed to its significance and potential applications in other fields. Many studies have reported that every part of the saffron plant has important benefits [13][14][15][16]. This growing consciousness is resulting in expanded uses of saffron in pharmacology, pharmacy, food science and technology, agronomy, microbiology, and horticulture, among other uses.…”
Section: Global Publication Trend (2000-2021)mentioning
confidence: 99%